To solve the problem step-by-step, let's go through each part.
Part A:
We start with the equation \( x^2 - 18x = -80 \). We want to rewrite it in the form \( x^2 - 18x + c = -80 + c \) so that the left side is a perfect square trinomial.
A perfect square trinomial can be formed using the formula: \[ (x - a)^2 = x^2 - 2ax + a^2 \] For our equation, \( -2a = -18 \) implies that \( a = 9 \) (since \( 2a = 18 \)).
To make this a perfect square trinomial, we need to add \( a^2 \) to both sides: \[ c = 9^2 = 81 \]
Thus, we replace \( c \) in our equation: \[ x^2 - 18x + 81 = -80 + 81 \]
So, \( c \) is:
Part A: \( c = 81 \)
Part B:
Now we rewrite the equation as: \[ x^2 - 18x + 81 = 1 \] The left-hand side \( x^2 - 18x + 81 \) can be factored as: \[ (x - 9)^2 = 1 \]
So, we have: Part B: \( (x - 9)^2 = 1 \)
Part C:
Next, we solve for \( x \): Taking the square root of both sides gives: \[ x - 9 = \pm 1 \] This results in two equations:
- \( x - 9 = 1 \) ⇒ \( x = 10 \)
- \( x - 9 = -1 \) ⇒ \( x = 8 \)
We need the lesser number: Part C: \( x = 8 \)
Part D:
Now, from the previous results, we find the greater number, which is: Part D: \( x = 10 \)
Summary of Answers:
- Part A: \( 81 \)
- Part B: \( (x - 9)^2 = 1 \)
- Part C: \( 8 \)
- Part D: \( 10 \)